NK cell defects in X-linked pigmentary reticulate disorder - Starokadomskyy, Petro (JCI Insight, 2019)
X-linked reticulate pigmentary disorder (XLPDR, Mendelian Inheritance in Man #301220) is a rare syndrome characterized by recurrent infections and sterile multiorgan inflammation. The syndrome is caused by an intronic mutation in POLA1, the gene encoding the catalytic subunit of DNA polymerase-α (Pol-α), which is responsible for Okazaki fragment synthesis during DNA replication. Reduced POLA1 expression in this condition triggers spontaneous type I interferon expression, which can be linked to the autoinflammatory manifestations of the disease. However, the history of recurrent infections in this syndrome is as yet unexplained. Here we report that patients with XLPDR have reduced NK cell cytotoxic activity and decreased numbers of NK cells, particularly differentiated, stage V, cells (CD3(–)CD56(dim)). This phenotype is reminiscent of hypomorphic mutations in MCM4, which encodes a component of the minichromosome maintenance (MCM) helicase complex that is functionally linked to Pol-α during the DNA replication process. We find that POLA1 deficiency leads to MCM4 depletion and that both can impair NK cell natural cytotoxicity and show that this is due to a defect in lytic granule polarization. Altogether, our study provides mechanistic connections between Pol-α and the MCM complex and demonstrates their relevance in NK cell function.